2005
DOI: 10.1519/00124278-200502000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Wearing a Cooling Jacket During Exercise Reduces Thermal Strain and Improvesendurance Exercise Performance in a Warm Environment

Abstract: Hasegawa, H., T. Takatori, T. Komura, and M. Yamasaki. Wearing a cooling jacket during exercise reduces thermal strain and improves endurance exercise performance in a warm environment. J. Strength Cond. Res. 19(1):122-128. 2005.-The aim of the present study was to investigate the effect of wearing a cooling jacket on thermoregulatory responses and endurance exercise performance in a warm environment. Nine untrained male subjects cycled for 60 minutes at 60% V O 2 max (Ex1) and then immediately exercised to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In the current study, the difference in m T sk after the 10 min of FAN wet intervention was 4.1 °C (60 min). A reduction in skin temperature leads to a reduction in peripheral skin blood, which results in a circulatory shift to central blood circulation [27] and may mitigate cardiovascular strain during exercise in the heat [28]. Some previous studies reported that a FAN wet cooling intervention during exercise in the heat reduces the HR [13,14].…”
Section: E96mentioning
confidence: 99%
“…In the current study, the difference in m T sk after the 10 min of FAN wet intervention was 4.1 °C (60 min). A reduction in skin temperature leads to a reduction in peripheral skin blood, which results in a circulatory shift to central blood circulation [27] and may mitigate cardiovascular strain during exercise in the heat [28]. Some previous studies reported that a FAN wet cooling intervention during exercise in the heat reduces the HR [13,14].…”
Section: E96mentioning
confidence: 99%